2013
DOI: 10.1002/bdd.1877
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic variability of flecainide in younger Japanese patients and mechanisms for renal excretion and intestinal absorption

Abstract: The aims of the present study were to evaluate the variability of pharmacokinetics of flecainide in young Japanese patients and to investigate the mechanisms of renal excretion and intestinal absorption of the drug using cultured epithelial cells. First the plasma concentration data of flecainide was analysed in 16 Japanese patients aged between 0.07 and 18.30 years using a one-compartment model. Considerable interindividual variability was observed in the oral clearance (CL/F) and the apparent volume of distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…All the STDD NMR samples contained 1 µM Pgp reconstituted into liposomes in 80% deuterated 100 mM KPi buffer, pD 7.4. For the STDD NMR experiments, a saturation transfer difference (STD) pulse sequence was used with a WATERGATE pulse sequence to suppress background water [46], with a 30 ms T1ρ spin lock filter to suppress background NMR signals and a train of 50 ms gaussian shaped selective pulses to excite the protein [47]. A total of 512 off-resonance spectra were subtracted from on-resonance spectra within the pulse program with a 2 sec saturation pulse by phase cycling at 40 and −1.5 ppm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…All the STDD NMR samples contained 1 µM Pgp reconstituted into liposomes in 80% deuterated 100 mM KPi buffer, pD 7.4. For the STDD NMR experiments, a saturation transfer difference (STD) pulse sequence was used with a WATERGATE pulse sequence to suppress background water [46], with a 30 ms T1ρ spin lock filter to suppress background NMR signals and a train of 50 ms gaussian shaped selective pulses to excite the protein [47]. A total of 512 off-resonance spectra were subtracted from on-resonance spectra within the pulse program with a 2 sec saturation pulse by phase cycling at 40 and −1.5 ppm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a large interindividual variability in systemic clearance and bioavailability of flecainide has been reported. This can be attributed to the genetic polymorphisms of CYP2D6, which metabolizes the drug in the liver, but also to functional variability in the transporters in the kidney (P-glycoprotein) and intestine (H+/tertiary amine antiporter) [13]. As far as median elimination half-life is concerned, Till et al described a significant linear correlation between elimination half-life of flecainide and age (r = 0.75; p < 0.01), both in case of oral and intravenous treatment [14].…”
Section: Discussionmentioning
confidence: 99%
“…Drug transporters mediate active renal tubular secretion through uptake in the basolateral membrane and efflux in the apical membrane of renal proximal tubules. 5) A previous in vitro study has reported that renal excretion of flecainide is associated with multidrug resistance protein 1 (MDR1) in the renal tubule. 6) Although organic cation transporter (OCT) 2 for basolateral uptake and multidrug and toxin extrusion (MATE) 1 and MATE2-K for apical efflux are also involved in the renal tubular secretion of cationic drugs, 5) the contribution of renal uptake and efflux transporters in active renal tubular secretion of flecainide, a cationic drug, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…5) A previous in vitro study has reported that renal excretion of flecainide is associated with multidrug resistance protein 1 (MDR1) in the renal tubule. 6) Although organic cation transporter (OCT) 2 for basolateral uptake and multidrug and toxin extrusion (MATE) 1 and MATE2-K for apical efflux are also involved in the renal tubular secretion of cationic drugs, 5) the contribution of renal uptake and efflux transporters in active renal tubular secretion of flecainide, a cationic drug, remains unclear. Because drug-drug interactions in renal excretion of flecainide may involve the inhibition of renal uptake and efflux transporters, it is important to understand the involvement of these transporters in renal tubular secretion of flecainide.…”
Section: Introductionmentioning
confidence: 99%